ABOUT SEMANTICS OF WORD FORMATION ON FRENCH MATERIAL - I. A. Tsybova (Vestnik MGIMO-Universiteta)
The purpose of the paper is to show how to study the semantics of word-formation by new paradigm. The intermediate character of word-formation is one of causes of the complexity of its semantics. Structural linguistics did not find the explanation of such questions as addition of the sense of derived words, semantics of polysemantic derived words by its methods. So these problems can be settled by new methods: cognitive paradigm (cognitivediscoursive approach) using such notions as concept, inference, proposition, prototype. Results: the derivational paradigm can be represented as a propositional structure and one of derivational type as the prototype of derivational category. Text facilitates to determine the meaning of polysemantic derived words. Thanks to inference we receive knowledge about words beyond the text. It is possible to deal with synonymic formants and antonymy of derived words. Each of these problems deserves to be studied separately.